2017
DOI: 10.3892/etm.2017.4449
|View full text |Cite
|
Sign up to set email alerts
|

Adult community-acquired pneumonia with unusually enlarged mediastinal lymph nodes: A case report

Abstract: Adult community-acquired pneumonia (ACAP) is the most prevalent pulmonary infectious disease that may be asymptomatic or have varying clinical presentations. Patients with ACAP often present with enlarged mediastinal lymph nodes on their chest computed tomography images. However, large irregular swollen lymph nodes are rarely reported in ACAP, and may therefore be confused with enlarged lymph node masses. In the present case report, the patient presented with lymph node masses, which were ameliorated to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This independent predictive value may strongly suggest that the addition of total lung involvement may be the most valuable risk factor of COVID-19 pneumonia progression. A recent study conducted a multicenter retrospective study involving patients with moderate COVID-19 pneumonia to investigate the utility of CT and clinical characteristics to risk-stratify the patients and found that CT score was associated with inflammatory levels and that older age, higher neutrophil-to-lymphocyte ratio (NLR), and CT score on admission are independent risk factors for short-term progression ( 37 ). Similar to this research, we also found the CT score differences between groups, while its predictive value was surpassed by quantitative CT parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This independent predictive value may strongly suggest that the addition of total lung involvement may be the most valuable risk factor of COVID-19 pneumonia progression. A recent study conducted a multicenter retrospective study involving patients with moderate COVID-19 pneumonia to investigate the utility of CT and clinical characteristics to risk-stratify the patients and found that CT score was associated with inflammatory levels and that older age, higher neutrophil-to-lymphocyte ratio (NLR), and CT score on admission are independent risk factors for short-term progression ( 37 ). Similar to this research, we also found the CT score differences between groups, while its predictive value was surpassed by quantitative CT parameters.…”
Section: Discussionmentioning
confidence: 99%